2014
DOI: 10.4028/www.scientific.net/amm.656.64
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Blockage Ratio on Detonation Flame Acceleration in Pulse Detonation Combustor Using CFD

Abstract: Detonation is the supersonic mode of combustion process which is essential for energy release from combustion process. Detonation is the more energetic process compare to deflagration mode of combustion process. The turbulence combustion flame cannot transit itself into detonation combustion process. So objective of this paper is to investigate the effect of obstacles configuration landed in detonation tube channel to propagate the detonation wave and diffraction encounters in an obstacles site. Four different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The effect of blockage ratio of 0.4, 0.5, 0.6 and 0.7 in channel for detonation wave acceleration are shown in Figure 4. The contour plot analysis shows the shock wave initiation and propagation time period in detonation tube is reduced by smaller blockage ratio of 0.5 [59]. Tripathi et al [60] computationally studied on effect of obstacle on flame propagation velocity.…”
Section: Results From Cfd Simulation and Calorimetric Analysismentioning
confidence: 99%
“…The effect of blockage ratio of 0.4, 0.5, 0.6 and 0.7 in channel for detonation wave acceleration are shown in Figure 4. The contour plot analysis shows the shock wave initiation and propagation time period in detonation tube is reduced by smaller blockage ratio of 0.5 [59]. Tripathi et al [60] computationally studied on effect of obstacle on flame propagation velocity.…”
Section: Results From Cfd Simulation and Calorimetric Analysismentioning
confidence: 99%
“…The temperature contour plots of detonation wave in obstructed detonation tube having blockage ratio of BR = 0.4, 0.5, 0.6, and 0.7 at obstacle spacing of = 4 cm are shown in Figure 17. The strong detonation wave propagation temperature of 3185 K was found in obstacle spacing of = 4 cm and detonation wave acceleration temperature greatly depends on blockage ratio; the strong propagation temperature increases the thermodynamic performance, which was found in blockage ratio of BR = 0.4 [132].…”
Section: Effect Of Obstacle Geometry On Detonation Wavementioning
confidence: 94%
“…The effect of blockage ratio on detonation flame acceleration was studied computationally. The obtained computational results showed that small blockage ratio is suitable for detonation flame acceleration and transition Debnath, P. et al [25]. Debnath P. et al [26,27] studied the ejector effect on detonation combustion wave in pulse detonation combustor.…”
Section: Introductionmentioning
confidence: 97%